Towards an Islamic stock market: a review of classical and modern literatures - Osmani, Noor Mohammad; Abdullah, Faruk (World Business Institute, 2009)
Share market plays an important role for the economic development of a nation. Companies and individuals purchase shares and bonds, and mostly uncertainties prevail over this market. The scholars, classical and modern, adopted different approach towards the validity or invalidity of such a market as it was not existent in the time of the Prophet or earlier generations. This paper tries to find its origin in Islamic Shari`ah to see its status and validity from Shari`ah perspective. Does stock market comply with the Shari`ah principles such as prohibition of Riba, Gharar, Qimar, and maintaining fairness in price and other rules? Does it contradict with Islamic ethical values such as ‘Adl,Amanah, sincerity, truthfulness, mutual cooperation and other values? The paper adopts an inductive and analytical approach to some of the available literatures from the traditional sources and also in modern writings on Islamic trade and finance. It is expected that the paper would shed some clear lights on the validity of the stock market, and if it is valid, how should it be.